2007
DOI: 10.1111/j.1467-8683.2007.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Dichotomous Worlds Hypothesis: towards a plurality of corporate governance logics

Abstract: The dichotomous worlds hypothesis holds that corporate governance systems worldwide are either based on the Anglo-American shareholder model or the Eurasian stakeholder model. We suggest a more fine-grained classification, based on five corporate governance logics - socially constructed, historical patterns of material practices, assumptions, values, beliefs, and rules by which all parties involved in economic productive activities structure their material interdependencies and provide meaning to the social re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 78 publications
3
34
0
Order By: Relevance
“…For example, GNP per capita went up rapidly in many emerging economies, and several countries reformed their minority shareholder protection regimes in the years following the 1997-1998 financial crisis (e.g., see Heugens & Otten, 2007). These temporal dynamics might possibly have affected our findings, especially since some contributors have suggested that minority shareholder expropriation is more prevalent during times of crisis than during business-as-usual periods (Johnson et al, 2000).…”
Section: Hypothesis Testingmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, GNP per capita went up rapidly in many emerging economies, and several countries reformed their minority shareholder protection regimes in the years following the 1997-1998 financial crisis (e.g., see Heugens & Otten, 2007). These temporal dynamics might possibly have affected our findings, especially since some contributors have suggested that minority shareholder expropriation is more prevalent during times of crisis than during business-as-usual periods (Johnson et al, 2000).…”
Section: Hypothesis Testingmentioning
confidence: 95%
“…The intuition behind this research question rests on the observation that nation-states have very different institutional configurations as a result of historically different development trajectories (Hollingsworth & Boyer, 1997). Rather than converging into a single "most efficient" capitalist system, these largely idiosyncratic development trajectories have culminated in geo-political "patchworks" in which several "varieties of capitalism" (Hall & Soskice, 2001) tend to durably coexist (Heugens & Otten, 2007). Country-level institutions play a large role in economic development, as they provide for (social) peace, assure individual freedoms to make investment and purchasing decisions, establish secure and transferable property rights, and enforce contracts through their legal systems (North, 1990).…”
Section: Country-level Moderating Effectsmentioning
confidence: 99%
“…Green et al, 2008). Heugens and Otten (2007) found that multiple Logics are embedded in the recommendations of corporate governance codes from around the globe, although there were differences between countries. In the USA, studies have documented a shift from Corporate Logic to Agency Logic (Jung, 2014;Rhee and Fiss, 2014;Zajac and Westphal, 2004), although this transition has been contested (Fiss, Kennedy and Davis, 2012;Green et al, 2008) and has given rise to practices that symbolically conform to Agency Logic (Joseph, Ocasio and McDonnell, 2014;Westphal and Graebner, 2010;Zajac and Westphal, 2004).…”
Section: An Institutional Logics Perspective On Corporate Governancementioning
confidence: 99%
“…On the other hand, a stronger position of blockholders is typical for Japan and (to smaller extent) to Germany; both legal systems are related, as Japan's law has German legal origins (La Porta et al, 2008). When we use Heugens and Otten's (2007) components (as defined above) to position the CEECA economies (see Figure 3 below), the latter come across as offering neither strong control rights to blockholders, nor organisational design that strengthens the auditing, nomination and remuneration functions of the boards.…”
Section: Corporate Governance Codesmentioning
confidence: 99%
“…Nevertheless, they do affect the behaviour of companies seeking finance on capital markets, given that the 'comply or explain' principle applies typically. While the provisions may also be extended to non-listed companies, the primary significance of the codes relates to listed firms (Aguilera and Cuervo-Cazurra, 2004;Heugens and Otten, 2007;Zattoni and Cuomo, 2008). Corporate governance codes are introduced by stock exchanges, governments, investors', director's, managers' or professional associations or a conjuncture of those (Aguilera and Cuervo-Cazurra, 2004) and provide uniform frameworks of reference.…”
Section: Corporate Governance Codesmentioning
confidence: 99%